Assessment of knowledge among diabetic patient on DM and its complications, benefits of compliance to scheduled clinic visits and impacts of missed appointments at MeTRH. - kanana, faith (Meru Universty of Science and Technology International Conference (MUSTIC), 2025)
ABSTRACT Background: Diabetes mellitus is a global health problem that affects individuals of all age groups. The disease is associated with complications that cause morbidity, mortality and huge economic burdens on the health care system. The main problem in the management of diabetes mellitus is non-compliance of patients to the management plan. Although cure is not expected with follow up, complications can be alleviated by achieving glycemic controls. The aim of the study was to assess the knowledge that diabetic patient attending the outpatient clinic have on DM and its complications, benefits of compliance to scheduled clinic visits and impacts of missed appointments at MeTRH. Methods: A cross-sectional survey was conducted among 100 diabetic patients attending the diabetic Outpatient Clinic at the Meru Teaching and Referral Hospital. Data was analyzed using descriptive statistics and inferential statistics. Results: The mean age of the participants was 39.83 years and the majority, (n=44, 59.5%) were females. The mean knowledge score was 46% with a standard deviation of ±29.3. Majority (49, 66.2%) of the respondents had poor general knowledge of diabetes, while (25, 33.8%) mentioned at least one correct aspect about diabetes mellitus. As for knowledge of diabetic complications, majority (45, 60.8%) knew at least one complication of diabetes mellitus, while (29, 39.2%) did not know of any complication. As for benefits of scheduled visits of care, (46, 62.2%) mentioned relevant benefits while (28, 37.8%) mentioned irrelevant benefits. Conclusions: Of the four areas assessed on knowledge diabetic patients had, there was generally poor knowledge by the participants. Recommendations: There is need to hold more sessions of routine health education to patients probably in the morning before normal clinic operations begin about diabetes, the importance of scheduled visits and the risks involved when one fails to comply. Key words: knowledge on diabetes mellitus and complications, missed visit impacts, compliance to scheduled visits